Knowledge Management and Theory of the Firm (Perspectivas em Ciência da Informação, 2009)
For a better understanding of the importance of knowledge management for enterprises, it is necessary to consider the theory of the firm. To accomplish their functions, the firms organize themselves in structures that aim at diminishing the costs of obtaining and exchanging information. This article discusses the role of information technologies in facilitating the exchange of information and knowledge among firms, as they enlarge firms possibilities of cooperation and affect their limits, creating new opportunities to knowledge management.